2019
DOI: 10.1590/1806-9282.65.5.731
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anthropometric parameters, and body image in adults: a systematic review

Abstract: SUMMARY OBJECTIVE: To evaluate the association between depression, anthropometric parameters and body image in adults through a systematic review of the literature. METHOD: Medline, Lilacs and PsycInfo databases were searched by two independent reviewers up to August 2018, without language restriction, including cross-sectional, case-control, and cohort studies in adults (18-65 years), of both genders. The quality of the studies was assessed using the Newcastle-Ottawa Scale instrument. The PRISMA standards w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 31 publications
(19 reference statements)
0
46
0
4
Order By: Relevance
“…In addition, a positive correlation between body mass index (BMI) and body dissatisfaction has been found. A considerable number of persons with overweight and obesity are dissatisfied with their bodies and wish they were thinner [3][4][5]. Women with obesity are significantly more dissatisfied with their bodies compared to men with obesity [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a positive correlation between body mass index (BMI) and body dissatisfaction has been found. A considerable number of persons with overweight and obesity are dissatisfied with their bodies and wish they were thinner [3][4][5]. Women with obesity are significantly more dissatisfied with their bodies compared to men with obesity [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…This finding adds to the mixed body of evidence evaluating misreporting of weight by mental well-being and warrants further study given that these factors have been identified as strong predictors of weight change. 27,28 Importantly, perceived weight status, arguably a composite measure encompassing subjective assessment of weight and psychosocial factors (e.g., perceptions and attitudes), was associated with measured weight even after adjustment.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16]27 Fewer studies have explored the potential role of mental well-being. 10,23,27,28 There is also evidence to suggest that the extent of misreporting and bias may differ across population subgroups. 3,20,26,29 Most germane to the present work are recent studies that have found that misreporting patterns differ in Hispanic and lowincome populations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these objective definitions, the perception of body image itself is highly influenced by biological, psychological and social factors. Furthermore, the components that easily affect the characterization of body image are Body Mass Index (Winter, Combs, & Ward, 2018), Family Pressure (Goodman, 2005), Societal and Peer Pressure (Al-Sheyab, Gharaibeh & Kheirallah, 2018), Media (Altaf, 2016), Social Media (Salomon & Brown, 2019), Self-Esteem (Kim, 2018), and many more (Silva, Ferriani & Viana, 2019). Shoraka, Amirkafi, and Garrusi (2019) explored further factors involved in influencing body image and its related disorders in which body dissatisfaction was found to be an inclining factor for serious health complications.…”
Section: Introductionmentioning
confidence: 99%